Motion Synthesis Of Planar Four Linkage Movement For Part Flipping Application - Mohd Najib , Ali Mokhtar; Nik Anwar, Nik Syahrim; Muhammad, Mohd Nazrin; Akiah, Masni-Azian; Yahaya, Saifudin Hafiz (2012)
Designs methods for four linkages encompass mathematical approach, trial and error method, function generation, motion synthesis and path synthesis. Various literatures found used mathematical approach to find specific solution. This main goal of this paper is to provide study of motion synthesis of four bar mechanism to find solution for mobile parts flipping application. Systematic procedures for motion synthesis to determine the length and position of the links in case of desired positions of a coupler are presented. The graphical method provides quick solution for designer regarding kinematic problem without involvement of complicated mathematical equation. Part of the solution is compared with mathematical approach and simulation approach. As a conclusion, the graphicaI approach result match with other method and helpful to provide better insight of the system during designing the solution.